STRENGTH ASSESSMENTS OF FIXED STEEL OFFSHORE PLATFORMS FOR LIFE EXTENSION - Sambu Potty, Narayanan (2013)
Currently, more than 80% of Malaysia’s offshore platforms are aged 30-40 years which exceeds the design life of 25 years. Structural assessments are needed for their extended use. The structural members of platforms are designed using API RP2A WSD, API RP2A LRFD and PTS 20.073. Rigidity of frame, use of nominal yield strength and presence of redundant members result in higher ultimate loads compared to the design load. Two common methods used for assessing existing platforms are the simplified ultimate strength analysis and static pushover analysis. Simplified ultimate strength is attained when any of member, joint, pile steel strength and pile soil bearing capacity reaches its ultimate capacity. Static pushover analysis generally concentrates on RSR and RRF for the ultimate strength. This report summarizes a study of the ultimate strength of 3 jacket platforms (Tripod, 4 and 8 legged) designed using API RP2A 21st Edition using SACS software. Several criteria of platform location, age, type, number of legs and other critical characteristics were considered. Three types of analyses have been carried out. First ultimate strength of platform with different number of legs is determined. 8 legged platforms have higher ultimate strength and stiffness compared to platforms with less number of legs. Secondly collapse load of platforms for different bracing configuration is studied. X-bracing contributes highest rigidity to the platform. Thirdly Redundant Member Analysis is done, which is a major step in the SIM. The priority for maintenance or repair due to damages to critical platform structural members due to vessel impact or corrosion is based on collapse analysis and collapse load factor. The collapse load factor when two members are damaged is also evaluated. The results of these studies are presented and conclusions drawn.